SAR village targets extraction and heterogonous image registration. Issue 21 (16th October 2019) - Li, Qixue; Yin, Kuiying
Abstract : Since the signal‐to‐noise ratio of synthetic aperture radar (SAR) image is low, it is difficult to match SAR images with optical images accurately. A new method of SAR village targets extraction and heterogonous image registration is proposed in this study. Median filter and partial differential method are first used to remove speckle noise; next, the grey level co‐occurrence matrix algorithm is used by calculating four typical texture parameters of it to obtain preliminary regions of interest (ROI) of village targets and false alarm areas are cleared by proposed local‐grey‐level congruency method; then proper numbers of Fourier descriptors and morphological algorithms are used to describe ROI again to maintain the boundary features of targets better. Finally, HU moment invariants, which is combined with Euclidean distance and cosine similarity measurements, are utilised to achieve heterogonous image registration. The experimental results show that the root‐mean‐square‐error of the registration image is small and the heterogonous registration image is accurate, demonstrating that the authors' method is stable and accurate, and owns certain research value and broad application prospect as well.